Investigation and evaluation of palygorskite microstructure following acid pretreatment and its potential use as an adsorbent for copper - Ahmed Flayyih Hussein; Mayssaa Ali Al-Bidry; Asawer A. AL Wasiti (Scientific Reports)
Abstract Palygorskite exhibits distinctive morphological and textural characteristics due to its fibrous and micropore nature. This research experimentally investigates the microstructure of palygorskite and how acid treatment changes the fibrous shape and ability to adsorb. Acetic and hydrochloric acid were used to study the effect of acid on palygorskite fibrous morphology. The effect of several factors, including acid type, hydrochloric acid concentration, mixing time, and temperature, on the efficiency of palygorskite in removing Cu was also studied. Different analytical techniques were used: scanning electron microscopy, field emission scanning electron microscopy, X-ray diffraction, X-ray fluorescence, particle size distribution, and zeta potential. Results illustrated that acetic acid effectively dispersed fibre aggregates, creating voids within the fibrous structure and reducing particle size while keeping the shape of the fiber. Hydrochloric acid led to varying degrees of structural changes. A concentration of 0.5, 1, and 2 M dispersed the fibre agglomerates and increased positive surface charge. Formation of an amorphous silica phase at 4 and 6 M, accompanied by a reduction in positive zeta potential. In general, acid pretreatment kept the morphology of the palygorskite fibre; however, 6 M HCl induced microfractures and roughness on the fibre rod. At room temperature and with a mixing time of one hour, the adsorption capacity of raw palygorskite for Cu was 298.4 ppm, while that of acetic acid pretreated palygorskite was 277.2 ppm. The primary decrease in Cu concentration occurred following palygorskite treatment with 0.5 M HCl to 212 ppm.